Gestão do conhecimento na Central de Atendimento ao Servidor da Pró-Reitoria de Gestão de Pessoas da Universidade Federal da Paraíba: um estudo utilizando a ferramenta Knowledge Management Diagnostic - Simão, Elani Santana de Oliveira (2015)
Public and private organizations are both experiencing a moment when the intellectual capital has become a source of differentiation and success for them to achieve their goals, so that they can produce wealth and a more important value than those ones previously generated by capital and labor. This new point of view is influenced by Knowledge Management (KM), which has raised the knowledge to an important administrative role in the organizational routine activities. In public service, KM has changed the focus of the sectors that deal with knowledge. With it, favorable conditions for creating new skills to improve efficiency and quality of services provided to citizens and society are being raised among the newest concerns of the managers. Given the above, this study aims to analyze GC practices in the Attendance Center for Civil Servants (CAS) of the Dean of Human Resources Management (PROGEP) of the Federal University of Paraiba (UFPB), and to raise subsidies that promote KM improvement initiatives for carrying out their activities. The research consisted of a case study of applied nature, descriptive and bibliographic character, and its target population was all CAS servers involved in care processes. The method used to gather data collection was the Knowledge Management Diagnostic (KMD) elaborated by Bukowitz and Williams (2002), which consists of a questionnaire containing 140 questions with indicators for appreciation of seven sections of the knowledge. The result analysis was based on documentary evaluations associated to methodological procedures and metrics criteria established by KMD method. In view of this, the final results enabled the recognition of shortcomings and gaps in the areas of KM, as well as indicate some initiatives for building an action plan in the section ‘Evaluate’ which got the lowest score - 57%. For this, we can see that CAS develops in approximate proportions KM initiatives in the seven sections of KMD, with performances considered acceptable in all sections of the method and, in addition, it reached 63 percentile points in the overall result. This performance is higher than that found by Bukowitz and Williams in their field tests, 55%. Although the results are favorably disposed to GC practices, it is clear that much remains to be done, because there is no official, regular or continuous process to facilitate the engagement and learning conditions to be part of the organizational culture of CAS.